1977
DOI: 10.1159/000180902
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative Glomerulonephritis in Monoclonal Gammopathy

Abstract: A 62-year-old white male suffering from plasmacytosis with monoclonal gammopathy developed gastrointestinal bleeding, microscopic hematuria, proteinuria and progressive azotemia. A renal biopsy demonstrated capillary wall thickening, mesangial hyperplasia, crescent formation and subepithelial humps. Serum immunoglobulin analysis showed IgG of lambda type. Serum complement, ANA, ASO titer and cryoglobulin were normal. It is suggested that proliferative glomerulonephritis with subepithelial humps should be added… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…There have been other reports in the older literature of patients with proliferative glomerulonephritis associated with circulating monoclonal IgG, without associated cryoglobulin activity [13][14][15][16]. Because these reports lacked description of either electron microscopic or immunofluorescence examination or both, it is uncertain whether these cases represent Randall type monoclonal immunoglobulin deposition disease, immunotactoid glomerulopathy, or are similar to the cases reported herein.…”
Section: Discussionmentioning
confidence: 73%
“…There have been other reports in the older literature of patients with proliferative glomerulonephritis associated with circulating monoclonal IgG, without associated cryoglobulin activity [13][14][15][16]. Because these reports lacked description of either electron microscopic or immunofluorescence examination or both, it is uncertain whether these cases represent Randall type monoclonal immunoglobulin deposition disease, immunotactoid glomerulopathy, or are similar to the cases reported herein.…”
Section: Discussionmentioning
confidence: 73%
“…The patient of Dharel al. [17], with lgG lambda myeloma, followed a similar, although more rapid course. More recently, Lapenas et al [18] reported on a patient with diabetes mellitus in whom rapidly progressive renal insufficiency revealed IgGkappa light chain myeloma and led to long-term hemodi alysis in 5 weeks.…”
Section: Commentsmentioning
confidence: 80%
“…A nodular glomerulopathy with thickening of glomerular and tubular basement membranes and mesangial deposits of kappa light chains has been described (Randall et al, 1976;Seymour et al, 1980;Gallo et al, 1980;Knobler et al, 1983). Sometimes more severe mesangial (Avashti et al, 1977) or intraand extra-capillary cell proliferation with crescent formation occurs (Kaplan & Kaplan, 1970;Dhar et al, 1977;Silva et al, 1980). The myeloma may have been associated with polyarteritis by chance, but seems more likely to have copyright.…”
Section: Discussionmentioning
confidence: 99%